-3+2x=-6x-91

Simple and best practice solution for -3+2x=-6x-91 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+2x=-6x-91 equation:


Simplifying
-3 + 2x = -6x + -91

Reorder the terms:
-3 + 2x = -91 + -6x

Solving
-3 + 2x = -91 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-3 + 2x + 6x = -91 + -6x + 6x

Combine like terms: 2x + 6x = 8x
-3 + 8x = -91 + -6x + 6x

Combine like terms: -6x + 6x = 0
-3 + 8x = -91 + 0
-3 + 8x = -91

Add '3' to each side of the equation.
-3 + 3 + 8x = -91 + 3

Combine like terms: -3 + 3 = 0
0 + 8x = -91 + 3
8x = -91 + 3

Combine like terms: -91 + 3 = -88
8x = -88

Divide each side by '8'.
x = -11

Simplifying
x = -11

See similar equations:

| 3x+7=6x-20 | | -7x-10=90+3x | | 2x+7=31+4x | | 4x-7=92-5x | | 3x+1=-11+6x | | 2+6x=7x-3 | | 6x+7=7+2x | | 4+3x=-3x+16 | | 4-7x=5x+148 | | (3+6g)12= | | 3x-9=7x-9 | | y=x^2+10x+16 | | 12+12y=10y-12 | | 4x-20+3x+15=100 | | 9-7x=-x-39 | | -5+3x=x-7 | | 9x+16=0 | | 2n(7n+8)=n+8 | | (x+a)(x+b)=(x+c)(x+d) | | 48-4x=5x+16 | | -28-10x=7x+23 | | 2x+10=-12-9x | | 4[3t+8]=3a+12 | | .2x-8=-2-1 | | [3x-7]-5=-3 | | x^4-12x^2-64=0 | | 5x-3=14x+5 | | 1.6q-4.5-4.5q=-3.9q-4.4 | | [5x+9]+6=1 | | 4x-20+3x+13=100 | | 4b-8=10-b | | x^4+8x^2+15=0 |

Equations solver categories